Оцінка точності місцеположення повітряних об’єктів у синхронних радіолокаційних мережах - Мачоніс, Т. С.; Обод, І. І. (ХНУРЕ, 2023)
The presented work considers the problems of assessing the impact of errors in the topological binding of receiving points of distributed airspace surveillance radar systems and the accuracy of the formation of time scales at the receiving points of the radar information synchronous system on the assessment of the coordinates of aerial objects.
Keywords: система радіолокаційного спостереження; синхронна інформаційна мережа; шкала часу